The impact of framing and groupthink to the career selection decision of accounting major students - Erina Sudaryati; Tri Angga Kusuma (Emerald Publishing Limited, 2018)
The purpose of this paper is to show the impact of framing and groupthink both individually and simultaneously regarding the decision of career selection.The samples of this study are determined by the purposive sampling method with accounting major students as the criteria. The number of observation is 178 accounting major students. Independent variables of the study are framing and groupthink, while the dependent variable is the career selection decision. Data used in this study are primary data that are obtained by questionnaire. The analysis techniques used are simple regression analysis, multiple linear regression and coefficient determination analysis.The results of this study show that framing has a positive effect on the career selection decision and so does the groupthink.Both framing and groupthink simultaneously have a positive effect on the career selection decision. The value of coefficient determination (R2) is 21.3 percent, and the rest of 78.7 percent is explained by non-researched variable.